Exploring the Subjective Well-Being of Mothers Raising Children with ADHD: A Mediation Model of Resilience, Parenting Self-Efficacy, and Social Support - Andayani, Sri Asih; Pudjibudojo, Jatie K; Tjahjono, Evy (Universitas Ahmad Dahlan, 2025)
Mothers of children with ADHD face complex parenting challenges that directly impact their subjective well-being (SWB). This study aims to examine the influence of parenting self-efficacy (PSE) and social support on SWB, with resilience serving as a mediating variable. A quantitative approach with a causal-comparative design was applied, and data were analyzed using Structural Equation Modeling (SEM). A total of 419 mothers of children with ADHD enrolled in inclusive elementary schools in Surabaya were selected through purposive sampling. The results revealed that PSE did not have a direct effect on SWB but showed a significant indirect effect through resilience. Similarly, social support did not directly influence SWB, but indirectly contributed to it via increased resilience. These findings suggest that resilience plays a central role as a psychological mechanism linking internal (PSE) and external (social support) resources to maternal well-being. This study offers practical contributions for developing family-based psychological interventions that prioritize resilience enhancement, as well as theoretical contributions by modeling multivariate relationships among psychological constructs in the context of neurodivergent families.